2022
DOI: 10.1108/maj-08-2021-3291
|View full text |Cite
|
Sign up to set email alerts
|

The impact of key audit matter reporting on analyst forecast accuracy and forecast dispersion: evidence from Chinese listed firms

Abstract: Purpose The purpose of this study is to investigate the decision usefulness of key audit matters (KAMs) disclosures from the perspective of financial analysts. Design/methodology/approach Using data from two groups of Chinese-listed firms subject to different audit standards, the authors use a quasi-natural experiment and the difference-in-differences approach to examine the impact of KAMs on analyst forecasts. The authors also conduct a textual analysis on management disclosures as well as on the content of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Therefore, they conclude that the effect of KAM disclosures on debt contracting is positive. In addition, Hu et al (2022) find that KAM disclosure was associated with a decline in financial analyst forecast errors and forecast dispersion with respect to firm earnings in China and Hong Kong compared to the results for firms not making such disclosures. This is a clear indication of the information impact of KAM disclosures on those whose intellectual product influences capital allocation.…”
Section: Introductionmentioning
confidence: 67%
“…Therefore, they conclude that the effect of KAM disclosures on debt contracting is positive. In addition, Hu et al (2022) find that KAM disclosure was associated with a decline in financial analyst forecast errors and forecast dispersion with respect to firm earnings in China and Hong Kong compared to the results for firms not making such disclosures. This is a clear indication of the information impact of KAM disclosures on those whose intellectual product influences capital allocation.…”
Section: Introductionmentioning
confidence: 67%
“…Impact of KAMs in the emerging Chinese capital market Since 2016, many scholars have focused on the information value of KAMs in the Chinese capital market. They found that communicating KAMs can improve cumulative abnormal returns (Wang et al, 2018), the quality of analysts' earnings forecasts (Hu et al, 2022;Kong et al, 2022) and firms' investment efficiency (Wang & Zou, 2022).…”
Section: Research On Kamsmentioning
confidence: 99%
“…Second, we contribute to research on how KAMs affect analysts' earnings forecasts. Unlike Kong et al (2022) and Hu et al (2022), we believe that auditors' interpretations of the risk of material misstatements can help analysts discern the quality of financial statements and, thus, improve the quality of analysts' forecasts. Third, we identify the conditions under which auditors' interpretations of the risk of material misstatements improve the quality of analysts' earnings forecasts in emerging markets.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations